Out from the shadows analytical feminist contributions to traditional philosophy - Crasnow, Sharon L.; Superson, Anita M. (Oxford : Oxford University Press, 2012)
This collection draws together 18 papers on topics in standard areas of traditional analytical philosophy, written from a feminist perspective. It brings out traditional philosophy by challenging it in a constructive, socially critical way that is essential for philosophy's fundamental goal of pursuing truth that matters.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes index.
Keywords: Analysis (Philosophy); Feminist theory